Effect of the application of litter conditioner on the udder health of dairy cows - Libis-Márta, Krisztina; Pajor, Ferenc; Póti, Péter (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
The aim of this study was to investigate the effect of bedding conditioner in cubical barn on somatic cell counts (SCC) of dairy cattle. The experiments were carried out in a commercial Holstein-Friesian farm in 2018. In this study, to evaluate the milk somatic cell counts of cows according to groups. In the case of one group litter was scattered on the cow mats in 100 g/ m2 every second day, and no treatment was applied for the other group as control. Somatic cell counts were measured each week between February and May. The supplementation of litter conditioner in this investigation resulted in better SCC values in experimental cows compared to the control group. The average somatic cell count was 123,875 cells/ml for the treated and 233,625 cells/ml for the control group, respectively. According to former experiments and results, such a small difference in the somatic cell counts causes measurable decrease in milk production and changes in milk composition even if these values are considered as normal levels.